Critical Thinking and Mathematical Problem Solving Skills of Students Through Schoology-Assisted Blended Learning Models - Pradana, Kenny Candra; Noer, Sri Hastuti (Universitas Wiralodra, 2023)
Students' poor critical thinking and mathematical problem-solving abilities are caused by a variety of variables, including teacher-centered learning and an ineffective learning models. In order to increase students' critical thinking skills and mathematical problem solving abilities, it is required to use an appropriate and unique learning strategy. The purpose of this research is to determine the influence of the Blended Learning models, as aided by Schoology Media, on students' critical thinking and mathematical problem-solving abilities. This study used a quasy experimental design as a research method. The population used in this study were all class X students of SMK-SMTI Bandar Lampung. The sample technique employed in this research was cluster random sampling, so that class X KI 4 as the experimental group and class X KI 1 as the control group, each group consisting of 28 students. The instruments used in this study were tests of critical thinking skills, tests of mathematical problem solving Skills, and documentation. Data analysis techniques using descriptive data analysis and inferential analysis. The hypothesis test is in the form of a One-way Multivariate Analysis of Variance (One-way MANOVA) Test. Based on the results of the analysis, 1) There is a difference between the Skills to think critically and the Skills to solve mathematical problems between the two groups of students; 2) There is a difference in the Skills to think critically between the group that is treated with the schoology-assisted Blended Learning model and the group that is given the conventional learning model treatment; 3) There are differences in the Skills to solve mathematical problems between groups that are treated with the schoology-assisted Blended Learning model and the group that is given the conventional learning model treatment; and 4) there is an influence between the Blended Learning learning model on students' critical thinking skills and mathematical problem solving.